The margin of appreciation in international human rights law deference and proportionality - Legg, Andrew, 1983- (Oxford : Oxford University Press, 2012)
International human rights courts accord their member states a margin of appreciation in relation to the implementation and interpretation of human rights law. This book argues that a degree of deference is justified - human rights inevitably look different from place to place.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Human rights